2017
DOI: 10.3389/fpls.2017.01197
|View full text |Cite
|
Sign up to set email alerts
|

Conserved Function of Fibrillin5 in the Plastoquinone-9 Biosynthetic Pathway in Arabidopsis and Rice

Abstract: Plastoquinone-9 (PQ-9) is essential for plant growth and development. Recently, we found that fibrillin5 (FBN5), a plastid lipid binding protein, is an essential structural component of the PQ-9 biosynthetic pathway in Arabidopsis. To investigate the functional conservation of FBN5 in monocots and eudicots, we identified OsFBN5, the Arabidopsis FBN5 (AtFBN5) ortholog in rice (Oryza sativa). Homozygous Osfbn5-1 and Osfbn5-2 Tos17 insertion null mutants were smaller than wild type (WT) plants when grown on Muras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 73 publications
(99 reference statements)
2
29
0
Order By: Relevance
“…The genomic structure and SNP analyses of the same FBN genes in the Chinse long and Gy14 lines indicated that the sequences of CsaFBN1 and CsaFBN9 are the most diverse ( Figure 2 ). Phylogenetic analysis showed that the 10 cucumber FBN genes identified in this study were divided into 10 groups, as was reported in Arabidopsis and rice [ 15 , 23 ], although no gene belonging to Group 5 ( FBN5 ) was found in the two cucumber genomes ( Table 1 , Figure 1 ). Plant FBN1 , FBN2 and FBN4 genes have been identified in many plants and have been reported to respond to abiotic stress [ 19 , 20 , 21 ].…”
Section: Discussionsupporting
confidence: 73%
See 4 more Smart Citations
“…The genomic structure and SNP analyses of the same FBN genes in the Chinse long and Gy14 lines indicated that the sequences of CsaFBN1 and CsaFBN9 are the most diverse ( Figure 2 ). Phylogenetic analysis showed that the 10 cucumber FBN genes identified in this study were divided into 10 groups, as was reported in Arabidopsis and rice [ 15 , 23 ], although no gene belonging to Group 5 ( FBN5 ) was found in the two cucumber genomes ( Table 1 , Figure 1 ). Plant FBN1 , FBN2 and FBN4 genes have been identified in many plants and have been reported to respond to abiotic stress [ 19 , 20 , 21 ].…”
Section: Discussionsupporting
confidence: 73%
“…Among the 10 cucumber FBN genes, the deduced protein sequence of CsaFBN1 (Csa6M512870.1) was identical to chromoplast-specific carotenoid-associated protein CHRC (Q96398) in the corollas of cucumber [ 11 , 40 ]. Compared with the number of FBN genes in other plant species, determined using conserved domain searches, cucumber has fewer than other plant species, such as Arabidopsis, with 14 genes [ 15 ] but a similar number to others, such as rice, with 11 genes [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations